Service Quality Impact on Customer Satisfaction at Amandit Loksado Lestari (ALL) Outbound Camp, South Kalimantan - Huda, Isra Ul; Sapar, Jhoni Fahrin; Harjanti, Wulandari (International Journal of Economics Studies, 2025)
This study investigates the impact of service quality on customer satisfaction at ALL Outbound Camp, a nature-based recreation destination in Loksado, South Kalimantan. Using the SERVQUAL model, which includes five dimensions of service quality—tangibles, reliability, responsiveness, assurance, and empathy—the research aims to identify which aspects most influence customer satisfaction. Data were collected through structured questionnaires and analyzed using descriptive statistics and linear regression. Findings reveal that service quality positively affects customer satisfaction, with responsiveness and assurance being the most significant dimensions. Based on these results, improvements in staff training and facility quality are recommended to enhance service delivery and overall visitor experience. This study provides insights valuable for ALL Outbound Camp management and contributes to the broader literature on service quality in nature-based tourism.